2006
DOI: 10.1016/j.jacc.2005.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification of In-Hospital Mortality for Coronary Artery Bypass Graft Surgery

Abstract: The risk index appears to be a valuable tool for predicting patient risk when applied to another year of New York data. It should now be tested against other risk indexes in a variety of geographical regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 15 publications
1
56
1
2
Order By: Relevance
“…Different factors, such as the small number of highrisk patients, the demographic differences of patients among different regions, differences in lifestyle and differences in the nature of data collection might have contributed to these findings. The fact that the risk factors for isolated CABG surgery are somewhat different than those for other open heart surgeries, particularly for valve surgery and combined surgery (18), might also have affected the prediction of mortality risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…Different factors, such as the small number of highrisk patients, the demographic differences of patients among different regions, differences in lifestyle and differences in the nature of data collection might have contributed to these findings. The fact that the risk factors for isolated CABG surgery are somewhat different than those for other open heart surgeries, particularly for valve surgery and combined surgery (18), might also have affected the prediction of mortality risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…Large US regional and national databases, such as the Northern New England Cardiovascular Disease Study Group, 3 the New York State cardiac surgery database, 4 and the Society of Thoracic Surgeons' National Cardiac Database (STS NCD), 5 have developed relatively sophisticated multivariable models to predict mortality risk across the entire spectrum of coronary artery bypass grafting (CABG) patients. Similar risk models have been developed outside the United States, most notably from the European Cardiac Surgery database.…”
Section: Article P 356mentioning
confidence: 99%
“…[1][2][3] In coronary artery bypass grafting (CABG), CKD is a complication in 12.2%-37% of patients. [4][5][6] In a cohort study on about 30,000 patients who underwent CABG, it was reported that the degree of postoperative increase in serum creatinine (sCr) is correlated with aggravation of CKD and mortality. 7) In a large multicenter study on 19,558 patients with CABG, the 5-year survival rate was 91.0% in non-CKD patients and 71.4% in CKD patients; CKD patients showed significantly lower rates.…”
Section: Introductionmentioning
confidence: 99%